Self-Aligned Hierarchical ZnO Nanorod/NiO Nanosheet Arrays for High Photon Extraction Efficiency of GaN-Based Photonic Emitter - Lee, Won-Seok (Micromachines (Basel), 2020)
Advancements in nanotechnology have facilitated the increased use of ZnO nanostructures. In particular, hierarchical and core–shell nanostructures, providing a graded refractive index change, have recently been applied to enhance the photon extraction efficiency of photonic emitters. In this study, we demonstrate self-aligned hierarchical ZnO nanorod (ZNR)/NiO nanosheet arrays on a conventional photonic emitter (C-emitter) with a wavelength of 430 nm. These hierarchical nanostructures were synthesized through a two-step hydrothermal process at low temperature, and their optical output power was approximately 17% higher than that of ZNR arrays on a C-emitter and two times higher than that of a C-emitter. These results are due to the graded index change in refractive index from the GaN layer inside the device toward the outside as well as decreases in the total internal reflection and Fresnel reflection of the photonic emitter.